Thidiazuron Triggers Morphogenesis in Rosa canina L. Protocorm-Like Bodies by Changing Incipient Cell Fate - Kou, Yaping; Yuan, Cunquan; Zhao, Qingcui; Liu, Guoqin; Nie, Jing; Ma, Zhimin; Cheng, Chenxia; Teixeira da Silva, Jaime A.; Zhao, Liangjun (Frontiers in Plant Science, 2016)
Thidiazuron (N-phenyl-N'-1,2,3-thiadiazol-5-ylurea; TDZ) is an artificial plant growth regulator that is widely used in plant tissue culture. Protocorm-like bodies (PLBs) induced by TDZ serve as an efficient and rapid in vitro regeneration system in Rosa species. Despite this, the mechanism of PLB induction remains relatively unclear. TDZ, which can affect the level of endogenous auxins and cytokinins, converts the cell fate of rhizoid tips and triggers PLB formation and plantlet regeneration in Rosa canina L. In callus-rhizoids, which are rhizoids that co-develop from callus, auxin and a Z-type cytokinin accumulated after applying TDZ, and transcription of the auxin transporter gene RcPIN1 was repressed. The expression of RcARF4, RcRR1, RcCKX2, RcCKX3, and RcLOG1 increased in callus-rhizoids and rhizoid tips while the transcription of an auxin response factor (RcARF1) and auxin transport proteins (RcPIN2, RcPIN3) decreased in callus-rhizoids but increased in rhizoid tips. In situ hybridization of rhizoids showed that RcWUS and RcSERK1 were highly expressed in columella cells and root stem cells resulting in the conversion of cell fate into shoot apical meristems or embryogenic callus. In addition, transgenic XVE::RcWUS lines showed repressed RcWUS overexpression while RcWUS had no effect on PLB morphogenesis. Furthermore, higher expression of the root stem cell marker RcWOX5 and root stem cell maintenance regulator genes RcPLT1 and RcPLT2 indicated the presence of a dedifferentiation developmental pathway in the stem cell niche of rhizoids. Viewed together, our results indicate that different cells in rhizoid tips acquired regeneration competence after induction by TDZ. A novel developmental pathway containing different cell types during PLB formation was identified by analyzing the endogenous auxin and cytokinin content. This study also provides a deeper understanding of the mechanisms underlying in vitro regeneration in Rosa.